Application of the Principle of Good Faith in the Implementation of Trademark Registration in Indonesia Based on the Supreme Court Decision Number 1051 K / PDT. SUS-HKI / 2023 - Winarsoputri, Annisa Wijayanti; Rokhim, Abdul; Isnaeni, Diyan (International Journal of Business, Law, and Education, 2024)
Brands contain a manufacturer's promise to consistently provide certain characteristics, benefits, and services to consumers. Economically, brands have a price that motivates producers in various ways so that the brand can compete and become popular among the public. The existence of legal rules on the protection of well-known trademarks can be applied to avoid losses to holders of trademark rights and for consumer protection against the purchase of counterfeit branded goods. The case contained in the Supreme Court Decision Number 1051 K/Pdt.Sus-HKI/2023 between Jolla and Jolla. Sus-HKI/2023 between Jollibee Food Corporation against Karsino in the "JOLLIBEE" trademark dispute is one example of bad faith in trademark registration in Indonesia. This research uses normative juridical method by using Statute Approach. The form of legal protection is in the form of cancellation of the Defendant's "JOLLIBEE" trademark from the General Register of Trademarks of the Directorate General of Intellectual Property Rights. The cancellation of the Defendant's "JOLLIBEE" trademark because there are similarities in essence with the Plaintiff's "JOLLIBEE" trademark.